2012
DOI: 10.1007/s00421-012-2488-4
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in purine metabolism in middle-aged elite, amateur, and recreational runners across a 1-year training cycle

Abstract: Changes in purine derivatives may be considered as signs of training-induced metabolic adaptations. The purpose of this study was to assess the effect of a 1-year training cycle on the response of hypoxanthine (Hx) concentration and Hx-guanine phosphoribosyltransferase (HGPRT) activity. Three groups of middle-aged male runners were examined: 11 elite master runners (EL; 46.0 ± 3.8 years), 9 amateur runners (AM; 45.1 ± 4.7 years), and 10 recreational runners (RE; 45.9 ± 6.1 years). Plasma Hx concentration and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
4
11
0
Order By: Relevance
“…Admittedly, the concentration of guanine nucleotides did not change throughout the annual training cycle in any studied group, but it was consistently higher in athletes comparing to the recreationally-trained runners. Similarly to previous studies [13][14][15], we showed that erythrocyte HGPRT activity peaked in the competition phase. Moreover, a gradual reduction in plasma Ino and Hx concentrations and increased plasma Ado concentration were visible in competitive athletes from the transition to the competition training phase.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Admittedly, the concentration of guanine nucleotides did not change throughout the annual training cycle in any studied group, but it was consistently higher in athletes comparing to the recreationally-trained runners. Similarly to previous studies [13][14][15], we showed that erythrocyte HGPRT activity peaked in the competition phase. Moreover, a gradual reduction in plasma Ino and Hx concentrations and increased plasma Ado concentration were visible in competitive athletes from the transition to the competition training phase.…”
Section: Discussionsupporting
confidence: 89%
“…In disciplines based on running, sprint and endurance training regimes have usually equal time frames but very different characteristics of training loads resulting from distinct training goals.Thus far, changes in erythrocyte energy status and purine nucleotide catabolites concentration were not yet explored also during a longer period or under prolonged training regime. Reports based on one-year training cycles only focused on changes in plasma hypoxanthine (Hx) concentration and erythrocyte hypoxanthine-guanine phosphoribosyltransferase (HGPRT) activity [13][14][15]. It was demonstrated that sprint training, predominated by high-intensity exercise, but also endurance training supplemented by high-intensity loads, led to a decrease in plasma Hx and an increase in erythrocyte HGPRT activity.…”
mentioning
confidence: 99%
“…Therefore, in this study that reported high levels of hypoxanthine, it can be concluded that ATP levels have not been renovated yet. Zielinski (2013), comparing groups of elite athletes and recreational amateurs, showed that elite athletes had a lower increase at hypoxanthine and xanthine rates and amateur and recreational athletes had more purine nucleotides excretion (9). Thus, in the case of the present study in which the participants had not been trained, it is likely that they were not able to recover appropriately during demolition and reconstruction of ATP in the training and recycling period (9).…”
Section: Discussionmentioning
confidence: 62%
“…In fact, it can be noted that higher HGPRT activity after high intensity training in which the dominant energy is anaerobic is an indicator of a better salvage pathway for reconstruction of adenine purine nucleotides (6). An increase in HGPRT after training has also been previously reported (9,15,25). It has also been indicated that in 4 seasons of the annual training cycle (adopted from Bompa, 1999), the match season in which the training moved towards anaerobic, the relaxing activity of this enzyme was high, and this is consistent with the findings of the present study because HIIT activities in which the major energy system is anaerobic can increase this enzyme and as a result, improve the salvage pathway purine nucleotides (26).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation